2019
DOI: 10.1128/jvi.00997-18
|View full text |Cite
|
Sign up to set email alerts
|

Eurasian Avian-Like Swine Influenza A Viruses Escape Human MxA Restriction through Distinct Mutations in Their Nucleoprotein

Abstract: To cross the human species barrier, influenza A viruses (IAV) of avian origin have to overcome the interferon-induced host restriction factor MxA by acquiring distinct mutations in their nucleoprotein (NP). We recently demonstrated that North American classical swine IAV are able to partially escape MxA restriction. Here we investigated whether the Eurasian avian-like swine IAV lineage currently circulating in European swine would likewise evade restriction by human MxA. We found that the NP of the influenza v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 24 publications
1
49
0
Order By: Relevance
“…In fact, the 2009 pandemic H1N1 virus features an MxA escape signature that is suggestive of porcine MX1 evasion (Manz et al 2013). Recent phylogenetic analyses revealed that the viral NP of the Eurasian avian-like swine lineage successively gained MxA escape mutations that increase the zoonotic potential of these viruses (Dornfeld et al 2019). It is conceivable that new MxA escape mutations in NP may arise in the future, be they located in the well-defined MxA sensitivity region (Manz et al 2013) or at novel sites as recently suggested by a deep mutational scanning approach (Ashenberg et al 2017).…”
Section: Mxa-mediated Iav Restriction and Escape Are Dictated By A Fementioning
confidence: 99%
“…In fact, the 2009 pandemic H1N1 virus features an MxA escape signature that is suggestive of porcine MX1 evasion (Manz et al 2013). Recent phylogenetic analyses revealed that the viral NP of the Eurasian avian-like swine lineage successively gained MxA escape mutations that increase the zoonotic potential of these viruses (Dornfeld et al 2019). It is conceivable that new MxA escape mutations in NP may arise in the future, be they located in the well-defined MxA sensitivity region (Manz et al 2013) or at novel sites as recently suggested by a deep mutational scanning approach (Ashenberg et al 2017).…”
Section: Mxa-mediated Iav Restriction and Escape Are Dictated By A Fementioning
confidence: 99%
“…In fact, all known human-adapted IAV strains encode specific adaptive mutations in NP, facilitating MxA escape (Mänz et al 2013;Ashenberg et al 2017). Importantly, the 2009 pandemic virus as well as the recently isolated Eurasian avian-like swine IAV highlight that these adaptive mutations can be acquired in functional Mx1-expressing intermediate hosts like swine (Mänz et al 2013;Dornfeld et al 2018). Intriguingly, the Mx1 proteins from Sturnira lilium and Carollia perspicillata, both bat influenza host species (Tong et al 2012(Tong et al , 2013, exert antiviral activity (Fuchs et al 2017).…”
Section: Is There a Zoonotic Risk?mentioning
confidence: 99%
“…MxA represents a considerable barrier against the zoonotic introduction of avian influenza viruses into the human population [7]. Interestingly, several investigations reported the antiviral properties of MxA from a human and mouse [10,20,21], porcine [22,23], and bovine [14,[24][25][26] origin. The interspecies transmission would have occurred when avian-origin IAV acquired certain mutations in the NP which overcome the MxA restriction [20,22,27].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several investigations reported the antiviral properties of MxA from a human and mouse [10,20,21], porcine [22,23], and bovine [14,[24][25][26] origin. The interspecies transmission would have occurred when avian-origin IAV acquired certain mutations in the NP which overcome the MxA restriction [20,22,27]. A few of these mutations were already found in circulating IAV strains before they were even reported to cross the species barrier [20,22], but in many cases, the adaptational mutations occurred subsequent to infection and transmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation